Immigrant concentration in schools: Consequences for native and migrant students - Nicole Schneeweis (Institute for the Study of Labor (IZA), 2013)
In this paper, I study the impact of immigrant concentration in primary schools on educational outcomes of native and migrant students in a major Austrian city between 1980-2001. The outcome measures of interest are track attendance after primary education and grade repetition. Using variation in the fraction of students with migration background among adjacent cohorts within schools and drawing special attention to time trends, the analysis shows that migrant students suffer from school-grades with a higher share of migrant students, while natives are not affected on average. These negative spill-over effects are particularly strong between students from the same area of origin, indicating that peer groups in schools form along ethnic dimensions.
Keywords: I21; J15; J24; 330; education; ethnic minorities; migrants; segregation; school choice